1961
DOI: 10.2172/4826330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Flux on the Corrosion of Aluminum by Water. Part Iii. Final Report on Tests Relative to the High-Flux Isotope Reactor

Abstract: The effect of very high heat fluxes on the corrosion of 1100 and 6061 aluminum alloys by water was investigated. The purpose of the investigation was to determine whether aluminum would have adequate corrosion resistance for use as a fuel-element cladding material in the High-Flux Isotope Reactor; therefore the test conditions generally simulated those expected to exist during reactor operation. At heat fluxes between 1 and 2 x lo6 E3tu/hr*ft2 and with coolant temperatures and velocities in the ranges of 131 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Postirradiation micrographs [1,5,8,[11][12][13] revealed that thin oxide films were free of cracks or pores, which suggested that the thermal conductivity degradation of thin oxides is negligible. As the oxide film thickened further, however, its thermal conductivity decreased due to porosity increase (or crack development).…”
Section: Model Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Postirradiation micrographs [1,5,8,[11][12][13] revealed that thin oxide films were free of cracks or pores, which suggested that the thermal conductivity degradation of thin oxides is negligible. As the oxide film thickened further, however, its thermal conductivity decreased due to porosity increase (or crack development).…”
Section: Model Developmentmentioning
confidence: 99%
“…As the oxide film thickened further, however, its thermal conductivity decreased due to porosity increase (or crack development). After reviewing the data [1][2][3][4][5][8][9][10][11][12][13]18], the threshold thickness was tentatively set at 25 lm. The decrease was assessed by an empirical function of the oxide thickness at a rate giving k T = 1.85 W/m-K at x = 50 lm, which was deduced from the data reported by Griess [1].…”
Section: Model Developmentmentioning
confidence: 99%
See 3 more Smart Citations